Validity and reliability of volleyball-specific reactive agility test - Amir, F.; Tomescu, G. (Science, Movement & Health, 2025)
Aim. In volleyball sport, a player must make motoric reactions based on visual information to perform fast and accurately. In the literature, it is seen that reactive agility test protocols are handled in accordance with the structure of the sport and arranged accordingly. In this context, the aim of this study is to determine the validity and reliability of a new reactive agility test designed for volleyball players.